Controllable velocity moment and prediction model for inlet guide vanes of a centrifugal pump. Issue 3 (8th May 2018) - Liu, Ming; Tan, Lei; Liu, Yabin; Xu, Yun; Cao, Shuliang
Abstract : Purpose: This paper aims to investigate the effect of three-dimensional (3D) inlet guide vanes (IGVs) on performance of a centrifugal pump. Design/methodology/approach: A design method for 3D IGVs is proposed based on the controllable velocity moment, which is determined by a fourth-order dimensionless function. Numerical simulation of the centrifugal pump with IGVs is carried out by solving the Reynolds-averaged Navier–Stokes equations. The method of frozen rotor is applied to couple the stationary and rotational domain. Findings: The efficiency of pump with 3D IGVs is higher than that with 2D IGVs for most prewhirl angles, which validate the advancement of 3D IGVs on prewhirl regulation. The effect of prewhirl regulation at small flow rate is more significant than that at large flow rate. Originality/value: A prediction model of velocity moment based on the Oseen vortex is proposed to describe the flow pattern downstream the IGVs.